STUDI FENOMENOLOGI KOMUNIKASI INTRAPRIBADI MAHASISWA DOMISILI JAKARTA DALAM PENGAMBILAN KEPUTUSAN UNTUK MELAKUKAN VAKSINASI COVID-19 - SYALWA SALVIA AZRI (2022)
The Covid-19 vaccination is a breakthrough that is present in Indonesia to overcome the Covid-19 Virus which has infected various circles of society. When the Covid-19 Vaccine was first introduced, various information emerged and raised news about the negative impact of the Covid-19 Vaccination. From the information, which reportedly cannot be confirmed, it has caused many public responses, one of which is regarding the safety of the Covid-19 vaccine. Based on data obtained from the results of the release of a survey related to Covid-19 and community behavior conducted by the Center for Strategic and International Studies (CSIS) Indonesia, on the Youtube channel (2021), it was stated that confidence in the efficacy of the Covid-19 vaccine was based on age 17-22 years. (Gen Z) 36.4% strongly believe or quite believe in the Covid-19 vaccine. Meanwhile, 63.6% have little or no confidence in the Covid-19 vaccine. From this data, this study was conducted to find out how the students experience of intrapersonal communication in making decisions to carry out Covid-19 vaccinations. The results of the study found major themes related to the experience of informants in making decisions for Covid-19 vaccination, namely: a) There is Doubt and Fear b) Vaccination Safety and Status c) Accessing Information About Covid-19 Vaccination d) Decisions Emerged Due to Encouragement from Outside Parties d) Differences in Perception Post-Covid-19 Vaccination